Moderation of Religiosity in Fashion Trends and Lifestyle on Muslimah Clothing Purchasing Decisions - Matondang, Zulaika; Nasution, Hamni Fadlilah; Panggabean, Asrani (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2024)
The increasingly diverse fashion trends for Muslim women's clothing have apparently not been able to increase the decision to purchase Muslim women's clothing among students at the Faculty of Islamic Economics and Business, UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan because it does not suit their passion and lifestyle, even though many Muslim women's fashion now follows fashion but also following current trends. The purpose of this research is to determine the influence of fashion trends and lifestyle on purchasing decisions for Muslim women's clothing with religiosity as the moderating variable. This research is quantitative research with primary data sources, and the sample used was 66 female respondents from the sharia economics study program class of 2019. The data analysis technique used prerequisite tests and moderated regression analysis (MRA) tests. The results of this research show that there is a partial influence between the fashion trend variable on purchasing decisions, and lifestyle on purchasing decisions. With the moderation test, the regression equation model two states that religiosity does not moderate the influence of fashion trends on purchasing decisions. The lifestyle variable with the third model regression equation moderation test states that religiosity is unable to moderate the influence of lifestyle on purchasing decisions.